Reimagining Sustainable Organization Perspectives on Arts, Design, Leadership, Knowledge and Project Management - Jevnaker, Birgit Helene; Olaisen, Johan (Springer International Publishing : Imprint: Palgrave Macmillan, 2022)
XV, 188 p. 11 illus., 1 illus. in color.